Application of Smart Contracts to Ensure Data Immutability and User Privacy in Gojek - Rizky Perwira; Afif Badawi; Hendri (Cattleya Darmaya Fortuna, 2026)
The evolution of blockchain technology establishes a novel paradigm for digital data management, underscoring transparency, security, and immutability. Centralized user data systems in ride-hailing platforms like Gojek are susceptible to breaches and manipulation. This study investigates the deployment of smart contracts to safeguard data immutability and augment user privacy via decentralization. Adopting a systematic literature review of recent blockchain applications in digital transportation, the results reveal that smart contract integration obviates central server dependency, automates transaction validation, and grants users complete sovereignty over personal data